Preparation method and application of low-chroma pyrosulfate boron trifluoride composite metal salt
By controlling the SO3 content in the pyrosulfate raw material and using dilute sulfuric acid, a low-color boron trifluoride composite metal salt of pyrosulfate is prepared, which solves the problems of increased color and decreased electrochemical performance caused by SO3 in the existing technology. The chromaticity stability of the electrolyte and the high-temperature performance of the battery are improved.
Patent Information
- Application Number
- CN202310883584.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
AI Technical Summary
The existing SO3 contained in the porsulfate boron trifluoride composite lithium salt during the preparation process leads to an increase in the color of the product, affecting the electrochemical performance of the battery, and catalyzed fluorination in the electrolyte, causing aggravation of discoloration.
By controlling the SO3 content in the pyrosulfate raw material to ≤500ppm, using dilute sulfuric acid as the raw material to reduce the SO3 content, and controlling the reaction conditions during the reaction process, a boron trifluoride composite metal salt of pyrosulfate with a color of ≤50 Hazen was prepared.
The prepared boron trifluoride composite metal salt of pyrosulfate is clear and transparent with high purity. When used in the electrolyte, it improves the color stability of the electrolyte and improves the high-temperature performance of the battery.
Smart Images

Figure CN119330368A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrolytes, and in particular to a preparation method of a low-chroma pyrosulfate boron trifluoride composite metal salt and application of the same in lithium ion battery electrolytes or sodium ion battery electrolytes. Background Art
[0002] As an indispensable component of the battery, electrolyte additives are mainly responsible for constructing a stable electrode / electrolyte interface film to achieve electronic insulation and facilitate the transmission of lithium ions / sodium ions. Under the influence of different functional groups in the additives, the composition and structure of the battery interface film change, ultimately affecting the battery's cycle life, high-temperature storage, and low-temperature discharge performance.
[0003] As the requirements for battery volume energy density become higher and higher, increasing the battery operating voltage and developing high-voltage electrolytes are the current mainstream methods, but high voltage will cause the various electrochemical properties of the battery to decay, which puts higher requirements on the performance of electrolyte additives. Furthermore, in order to simultaneously meet the working performance of the battery in high-temperature and low-temperature environments, the electrolyte is required to have both excellent high-temperature and low-temperature performance. At present, most electrolyte additives only have high-temperature performance or low-temperature performance unilaterally, and a combination of high-temperature additives and low-temperature additives is required to simultaneously meet the high and low-temperature performance of the battery.
[0004] Pyrosulfate boron trifluoride composite lithium salt is a new electrolyte additive with both high and low temperature performance developed by Zhejiang Chemical Research Institute Co., Ltd. Its patent CN202211375099.4 discloses the use of disiloxane sulfate and lithium hexafluorophosphate as raw materials to prepare lithium pyrosulfate, and then its patent CN202211583064.X further reacts the lithium pyrosulfate with boron trifluoride gas or boron trifluoride complex to obtain pyrosulfate boron trifluoride composite lithium salt, which can simultaneously improve the battery's cycle performance, high temperature storage performance and low temperature performance. However, the pyrosulfate boron trifluoride composite lithium salt prepared by this preparation method is reddish brown, and its application in the electrolyte also has a certain impact on the chromaticity stability of the electrolyte. Summary of the invention
[0005] In order to solve the above technical problems, the present invention has found through research that the pyrosulfate boron trifluoride composite lithium salt prepared by using different preparation methods as raw materials has different chromaticity. Further research found that the SO contained in the lithium pyrosulfate raw material 3 It will increase the color of the product and affect the electrochemical performance of the battery when using the lithium pyrosulfate boron trifluoride composite salt. The reason is speculated to be: on the one hand, the SO contained in the lithium pyrosulfate raw material 3During the synthesis process, the lithium boron trifluoride pyrosulfate salt product will be decomposed, which will increase the color of the product. On the other hand, the SO contained in the lithium pyrosulfate raw material 3 In the process of synthesis and preparation, it is inevitably transferred to the pyrosulfate boron trifluoride composite lithium salt product, and SO 3 It has strong oxidizing properties. When pyrosulfate boron trifluoride complex lithium salt is applied to the electrolyte, the oxidizing substances can catalyze the fluorination of solvent molecules to form higher molecular weight fluorinated polymers, which intensifies the discoloration of the electrolyte and also leads to the degradation of the electrochemical performance of the battery. The battery cycle performance and high-temperature storage performance will be significantly reduced.
[0006] In addition, the present invention further studies and verifies that sodium pyrosulfate boron trifluoride salt and lithium pyrosulfate boron trifluoride salt have the same properties and phenomena.
[0007] Therefore, the present invention proposes a method for preparing a low-chroma pyrosulfate boron trifluoride composite metal salt. The pyrosulfate boron trifluoride composite metal salt prepared by the preparation method is clear and transparent with high purity. When used in an electrolyte, the discoloration problem of the electrolyte is improved, and the high-temperature performance of the battery is further improved.
[0008] The objective of the present invention is achieved through the following technical solutions:
[0009] A method for preparing a low-chromaticity pyrosulfate boron trifluoride composite metal salt, the preparation method comprising: using SO 3 A pyrosulfate with a content of ≤500ppm is used as a raw material, and reacts with boron trifluoride gas or a boron trifluoride complex to obtain a reaction solution with a chromaticity of ≤50 Hazen, wherein the reaction solution at least comprises a pyrosulfate boron trifluoride composite metal salt with a structure shown in the following formula (I-1):
[0010]
[0011] In formula (I-1), M is Li or Na; preferably, M is Li.
[0012] Taking the preparation of pyrosulfate boron trifluoride composite lithium salt as an example, the reaction formula is as follows:
[0013]
[0014] Preferably, SO 3 The pyrosulfate with a content of ≤200ppm is used as a raw material to prepare a reaction solution with a chromaticity of ≤20 Hazen.
[0015] Generally, as long as the SO in the pyrosulfate raw material is 3 Content ≤200ppm, while controlling POF 3By reducing the content of acidic gas impurities such as fluorine silane, a low-color pyrosulfate boron trifluoride composite metal salt can be obtained.
[0016] In a preferred embodiment, the pyrosulfate raw material of the present invention is prepared by the following steps:
[0017] (1) a step of preparing bisulfate: an inorganic salt and dilute sulfuric acid are reacted to obtain bisulfate, wherein the inorganic salt is selected from at least one of sulfate, metal oxide, carbonate, metal hydroxide or bicarbonate; and the bisulfate is lithium bisulfate or sodium bisulfate;
[0018] Taking lithium sulfate as an inorganic salt as an example, the reaction formula is as follows:
[0019] Li 2 SO 4 +H 2 SO 4 →2LiHSO 4
[0020] (2) a pyrosulfate preparation step: a hydrogen sulfate solid is decomposed by heat to obtain a pyrosulfate; the pyrosulfate is lithium pyrosulfate or sodium pyrosulfate;
[0021] Taking lithium bisulfate as an example, the reaction formula is as follows:
[0022] .
[0023] In step (1), the present invention uses dilute sulfuric acid as raw material, which avoids the use of SO 3 / concentrated sulfuric acid / fuming sulfuric acid as raw materials, and more importantly, it can reduce the SO in the prepared pyrosulfate raw materials. 3 Specifically, the mass concentration of dilute sulfuric acid is 10-65wt%. In actual operation, dilute sulfuric acid of corresponding concentration can be directly used, or sulfuric acid of slightly higher concentration can be used and diluted with deionized water. Preferably, the mass concentration of dilute sulfuric acid is 15-40wt%.
[0024] In step (1), the molar ratio of the inorganic salt to the dilute sulfuric acid is (0.8-1.2):1, preferably (0.9-1.1):1, and more preferably about 1:1. At the same time, the reaction temperature in step (1) is controlled to be 0-80°C, and the reaction time is 0.5-24h; preferably the reaction temperature is 20-45°C, and the reaction time is 2-4h. By controlling the molar ratio of sulfate to dilute sulfuric acid, as well as the reaction temperature and time, the reaction product of step (1) is basically bisulfate, so the reaction product can be directly heated and dried to remove moisture and used in the next step.
[0025] In step (2), the hydrogen sulfate solid is calcined at 100-300°C for 0.5-72h to obtain pyrosulfate; preferably, the hydrogen sulfate solid is calcined at 130-250°C for 2-36h to obtain pyrosulfate; more preferably, the hydrogen sulfate solid is heated at 160-200°C for 4-12h to obtain pyrosulfate. The purity of the pyrosulfate obtained is different depending on the calcination temperature. If the calcination temperature is too high, the product contains more sulfate impurities and SO 3 If the calcination temperature is too low, the conversion of hydrogen sulfate is incomplete and the sample contains more H 2 O.
[0026] In a specific operation, in order to improve the reaction effect, before the hydrogen sulfate is heated and decomposed, the hydrogen sulfate solid obtained in step (1) is first ground to obtain a uniform white powder, which is then placed in a heating device (such as a muffle furnace) for calcination and decomposition to obtain a pyrosulfate raw material.
[0027] In the preparation process of the pyrosulfate boron trifluoride composite metal salt, the reaction solvent is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl acetate, ethyl acetate, methyl propionate, γ-butyrolactone, ether, ethylene glycol dimethyl ether, acetonitrile, benzyl cyanide or propionitrile. Considering the application of the pyrosulfate boron trifluoride composite metal salt in the electrolyte, the reaction solvent is preferably a commonly used solvent in the electrolyte, such as at least one of dimethyl carbonate, ethyl methyl carbonate or diethyl carbonate.
[0028] The substance reacting with the pyrosulfate may be either boron trifluoride gas or a boron trifluoride complex. The boron trifluoride complex is selected from at least one of a boron trifluoride ethyl ether complex, a boron trifluoride glycol dimethyl ether complex, a boron trifluoride dimethyl carbonate complex, a boron trifluoride pyridine complex, a boron trifluoride ethylamine complex, a boron trifluoride butyl ether complex, a boron trifluoride methyl ether complex, a boron trifluoride acetonitrile complex, a boron trifluoride piperidine complex, a boron trifluoride phenol complex, a boron trifluoride tetrahydrofuran complex, a boron trifluoride dimethyl sulfide complex or a boron trifluoride morpholine complex.
[0029] During the reaction of pyrosulfate with boron trifluoride gas or boron trifluoride complex, the molar ratio of pyrosulfate to boron trifluoride gas or boron trifluoride complex is (0.33-1.0):1, the reaction temperature is 40-70°C, and the reaction time is 5-24h; preferably, the reaction temperature is 50-70°C, and the reaction time is 5-12h.
[0030] Under the preparation process of the present invention, different reaction temperatures, different material ratios and other factors may cause the reaction solution to include at least one of the compounds represented by the following formulas (I-2), (I-3), (I-4), (I-5) and (I-6) in addition to the pyrosulfate boron trifluoride composite metal salt having the structure represented by formula (I-1):
[0031]
[0032]
[0033] In formulas (I-2), (I-3), (I-4), (I-5), and (I-6), M is Li or Na.
[0034] Specifically, the reaction liquid contains at least 80wt% of the pyrosulfate boron trifluoride complex metal salt with the structure represented by the formula (I-1); preferably, the reaction liquid contains 80 to 95wt% of the pyrosulfate boron trifluoride complex metal salt with the structure represented by the formula (I-1), and the rest is at least one of the compounds represented by the above formulas (I-2), (I-3), (I-4), (I-5), and (I-6).
[0035] The present invention also provides the use of a low-chroma pyrosulfate boron trifluoride composite metal salt prepared by any of the above-mentioned preparation methods in an electrolyte, the application comprising: adding the prepared low-chroma pyrosulfate boron trifluoride composite metal salt to an electrolyte so that its mass percentage in the electrolyte is 0.01-15.0wt%. In a preferred embodiment, the mass percentage of the prepared pyrosulfate boron trifluoride composite metal salt in the electrolyte is 0.1-10.0wt%; more preferably, the mass percentage of the prepared pyrosulfate boron trifluoride composite metal salt in the electrolyte is 0.1-5.0wt%; more preferably, the mass percentage of the prepared pyrosulfate boron trifluoride composite metal salt in the electrolyte is 0.1-3.0wt%.
[0036] The electrolyte obtained by adding the pyrosulfate boron trifluoride composite metal salt can be used in lithium ion secondary batteries or sodium ion secondary batteries to improve the battery's cycle performance at high voltage and high temperature, high temperature storage performance and low temperature cycle performance.
[0037] In a specific embodiment, the pyrosulfate boron trifluoride composite metal salt is a pyrosulfate boron trifluoride composite lithium salt, which is added to the electrolyte of a lithium ion battery for application. The active material of the positive electrode of the lithium ion secondary battery is selected from a nickel-cobalt-manganese ternary material, a nickel-cobalt-aluminum ternary material, a lithium cobaltate material or a lithium iron phosphate material, and the active material of the negative electrode is selected from graphite, silicon carbon, silicon dioxide, silicon, tin, metallic lithium or a composite material thereof.
[0038] In another specific embodiment, the pyrosulfate boron trifluoride composite metal salt is a pyrosulfate boron trifluoride composite sodium salt, which is added to the sodium ion battery electrolyte for application. The active material of the positive electrode plate of the secondary sodium ion battery is selected from NaMn (1-x-y) Ni y M x O 2 (0 ≤ x, y ≤ 1, M is Cu, Fe, Co), sodium manganate, sodium vanadium phosphate, sodium fluorovanadate phosphate, sodium iron phosphate, sodium manganese phosphate, Na x MnFe(CN) 6 (0 < x ≤ 2) and at least one of them. The active material of the negative electrode plate is selected from at least one of hard carbon, carbon black, amorphous carbon, graphite, SnS 2 , Na 2 Ti 3 O 7 , silicon-based materials, metal oxides, metal sulfides or metallic sodium.
[0039] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0040] 1. The preparation process of the present invention obtains pyrosulfate with low SO 3 content. Using this pyrosulfate as a raw material, a pyrosulfate boron trifluoride composite metal salt that is clear, transparent and has a chromaticity ≤ 50 Hazen is obtained; using this pyrosulfate boron trifluoride composite metal salt as an additive in the electrolyte, the discoloration problem of the electrolyte is improved, and the electrochemical performance of the battery is enhanced. In particular, the improvement effects on high-temperature performance such as suppressing gas generation during high-temperature storage of the battery, improving high-temperature capacity retention and recovery rate are more obvious.
[0041] 2. The pyrosulfate prepared by the preparation process of the present invention not only has low SO 3 content, but also does not contain substances such as POF 3 , fluorosilane, etc. The overall operation is simple, the raw material cost is low, it is safe and environmentally friendly, and it is suitable for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Att Figure 1 ached is the 19 F-NMR spectrum of the 1# lithium salt prepared in Example 1 of the present invention;
[0043] Att Figure 2 ached is the 11 B-NMR spectrum of the 1# lithium salt prepared in Example 1 of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0044] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments. Those skilled in the art should recognize that the present invention covers all possible alternatives, improvements and equivalents within the scope of the claims.
[0045] Example 1
[0046] This embodiment provides a method for preparing a pyrosulfate boron trifluoride composite lithium salt, which specifically includes the following steps:
[0047] S1. Add 1 mol Li 2 SO 4 (purity 99.5%), and then add 20wt% H 2 SO 4 491.27 g, stir to mix the system evenly, react at 25 ° C for 4 h, and obtain LiHSO 4 Reaction solution: the LiHSO 4 The reaction solution was evaporated and heated to remove water to obtain LiHSO 4 solid;
[0048] S2.LiHSO 4 The solid was ground evenly into a white powder, and then LiHSO 4 The powder was placed in a crucible in a muffle furnace and calcined at 150°C for 10 h to obtain lithium pyrosulfate solid. IC (ion chromatography test) was used to detect SO in lithium pyrosulfate solid. 3 The content of SO in the prepared lithium pyrosulfate solid is determined according to the test results. 3 The content is 124ppm.
[0049] S3. In a drying room with a dew point of -40°C, add 0.2 mol of lithium pyrosulfate (purity 99%) prepared in step S2 into the reaction bottle, use dimethyl carbonate as solvent, start stirring to mix the system evenly; then introduce 0.4 mol of boron trifluoride gas into the reaction bottle, react at 50°C for 5h, and obtain a pyrosulfate boron trifluoride complex lithium salt reaction liquid; use reduced pressure distillation to remove the reaction solvent and residual unreacted boron trifluoride, the reduced pressure distillation temperature is controlled at 60°C, and the time is controlled to 0.5h, to obtain a pyrosulfate boron trifluoride complex lithium salt, recorded as 1# lithium salt.
[0050] According to the SJ / T11723-2018 industry standard document test method, a colorimeter was used to detect the chromaticity. The test results showed that the chromaticity of 1# lithium salt was 15.6 Hazen.
[0051] At the same time, NMR F spectrum and NMR B spectrum are used to detect the composition of the product. LiBF 4 Standard samples were used for comparison; NMR F spectra were adopted 19 F-NMR was used for testing, and the nuclear magnetic B spectrum was used 11 B-NMR test. Figure 1 and attached Figure 2 The NMR F spectrum and NMR B spectrum of 1# lithium salt are given, such as Figure 1 , 2 As shown, the peak positions of the NMR F spectrum are as follows:
[0052] Compound (I-1, M is Li): δ = -151.05 ppm
[0053] Compound (I-2, M is Li): δ = -146.83 ppm
[0054] The peak positions of the NMR B spectrum are shown below:
[0055] Compound (I-1, M is Li): δ = -0.75 ppm
[0056] Compound (I-2, M is Li): δ = -1.12 ppm
[0057] Standard sample LiBF 4 The NMR F spectrum peak δ = -156.69ppm; the NMR B spectrum peak δ = -1.02ppm.
[0058] To verify and confirm the compounds, compound (I-1, M is Li) and compound (I-2, M is Li), as well as LiBF 4 Theoretical calculations were performed. The DFT / B3LYP function and 6-31** basis set were used to optimize the structure of the compound, and the DFT / B3LYP function and 6-311** basis set were used to calculate the nuclear magnetic peak position of the above compound. The calculation results were compared with the test results, as well as LiBF 4 The NMR peak positions of the standard sample (F: δ = -156.69ppm, B: δ = -1.02ppm) were analyzed in coordination, and matched the above NMR spectrum results, which had a high degree of credibility. Therefore, it can be confirmed that the 1# lithium salt is mainly compound I-1 (M is Li) and also contains compound I-2 (M is Li).
[0059] By integrating and calculating the peak area of the NMR F spectrum, it can be seen that in the 1# lithium salt, excluding the amount of dimethyl carbonate, the mass content of compound (I-1, M is Li) is 95.84wt%, and the mass content of compound (I-2, M is Li) is 4.16wt%. Further area integration conversion is performed through the B spectrum, and it is found that the calculation results are consistent with the F spectrum, and the calculation reliability is high.
[0060] Example 2
[0061] The operation of this embodiment is the same as that of embodiment 1, except that the reaction temperature in step S3 is adjusted from 50° C. to 70° C. After step S3, a pyrosulfate boron trifluoride composite lithium salt is obtained, which is recorded as 2# lithium salt.
[0062] According to IC test, SO in lithium pyrosulfate solid 3 The content is 189ppm; the chromaticity of 2# lithium salt tested by colorimeter is 25.1Hazen.
[0063] Test on 2# lithium salt 19 F-NMR and 11 B-NMR, and using LiBF 4 Compared with the standard sample, the positions of the NMR F and B peaks are shown below:
[0064] Compound (I-1, M is Li): peaks were observed at δ=-151.05 ppm in the NMR F spectrum and at δ=-0.75 ppm in the NMR B spectrum.
[0065] Compound (I-3, M is Li): Peaks were observed in the NMR F spectrum at δ = -150.65ppm, δ = -144.52ppm, and the peak area integration ratio was 3:1; peaks were observed in the NMR B spectrum at δ = -0.67ppm, and the B spectrum at δ = -0.36ppm, and the peak area integration ratio was 2:1.
[0066] Compound (I-4, M is Li): Peaks were observed in the NMR F spectrum at δ = -150.39 ppm, δ = -144.0 ppm, and the peak area integration ratio was 1.5:1; peaks were observed in the NMR B spectrum at δ = -0.65 ppm, δ = -0.26 ppm, and the peak area integration ratio was 1:1.
[0067] Standard sample LiBF 4 : A peak was observed in the NMR F spectrum at δ = -156.69 ppm; a peak was observed in the NMR B spectrum at δ = -1.02 ppm.
[0068] To verify and confirm the compounds, compounds (I-1, I-3, I-4, M is Li) and LiBF 4 Theoretical calculations were performed. The DFT / B3LYP function and 6-31** basis set were used to optimize the structure of the compound, and the DFT / B3LYP function and 6-311** basis set were used to calculate the nuclear magnetic peak position of the above compound. The calculation results were compared with the test results, as well as LiBF 4 The NMR peak position of the standard sample (F: δ = -156.69ppm, B: δ = -1.02ppm) was analyzed in coordination. It matches the above NMR results and has a high degree of credibility. Therefore, it can be confirmed that product 1 #The main compound is I-1 (M is Li), and it also includes compounds I-3 (M is Li) and I-4 (M is Li).
[0069] By integrating and calculating the peak area of the NMR F spectrum, it can be seen that in the 2# lithium salt, excluding the amount of dimethyl carbonate, the mass content of compound (I-1, M is Li) is 84.6wt%, the mass content of compound (I-3, M is Li) is 9.1wt%, and the mass content of compound (I-4, M is Li) is 6.3wt%. Further area integration conversion is performed through the B spectrum, and it is found that the calculation results are consistent with the F spectrum, and the calculation reliability is high.
[0070] Example 3
[0071] The operation of this embodiment is the same as that of embodiment 1, except that in step S1, 1 mol Li 2 CO 3 (Purity 99.5%) replaces 1 mol Li 2 SO 4 , and other operations remain unchanged. The pyrosulfate boron trifluoride composite lithium salt is prepared and recorded as 3# lithium salt.
[0072] According to IC test, SO in lithium pyrosulfate solid 3 The content is 177ppm; the chromaticity of 3# lithium salt tested by colorimeter is 23.5Hazen.
[0073] By integrating and calculating the peak area of the NMR F spectrum, it can be seen that in the 3# lithium salt, excluding the amount of dimethyl carbonate, the mass content of compound (I-1, M is Li) is 92.6wt%, and the mass content of compound (I-2, M is Li) is 7.4wt%. Further area integration conversion is performed through the B spectrum, and it is found that the calculation results are consistent with the F spectrum, and the calculation reliability is high.
[0074] Example 4
[0075] The operation of this embodiment is the same as that of embodiment 1, except that in step S2, the calcination temperature is increased from 150° C. to 190° C., and other operations remain unchanged. A pyrosulfate boron trifluoride composite lithium salt is prepared, which is recorded as lithium salt #4.
[0076] According to IC test, SO in lithium pyrosulfate solid 3 The content is 372ppm; the chromaticity of 4# lithium salt tested by colorimeter is 45.1Hazen.
[0077] By integrating and calculating the peak area of the NMR F spectrum, it can be seen that in the 4# lithium salt, excluding the amount of dimethyl carbonate, the mass content of compound (I-1, M is Li) is 90.3wt%, and the mass content of compound (I-2, M is Li) is 9.7wt%. Further area integration conversion is performed through the B spectrum, and it is found that the calculation results are consistent with the F spectrum, and the calculation reliability is high.
[0078] Example 5
[0079] The operation of this embodiment is the same as that of embodiment 1, except that in step S1, the concentration of dilute sulfuric acid is adjusted by adding 40 wt % H 2 SO 4 270.21 g, other operations remain unchanged. The pyrosulfate boron trifluoride composite lithium salt is prepared and recorded as 5# lithium salt.
[0080] According to IC test, SO in lithium pyrosulfate solid 3 The content is 316ppm; the chromaticity of 5# lithium salt tested by colorimeter is 42.6Hazen.
[0081] By integrating and calculating the peak area of the NMR F spectrum, it can be seen that in the 5# lithium salt, excluding the amount of dimethyl carbonate, the mass content of compound (I-1, M is Li) is 94.3wt%, and the mass content of compound (I-2, M is Li) is 5.7wt%. Further area integration conversion is performed through the B spectrum, and it is found that the calculation results are consistent with the F spectrum, and the calculation reliability is high.
[0082] Example 6
[0083] The operation of this embodiment is the same as that of embodiment 1 except that: 2 SO 4 Replaced by Na 2 SO 4 , other operations remain unchanged. After steps S1 and S2, sodium pyrosulfate solid is prepared. After step S3, pyrosulfate boron trifluoride composite sodium salt is obtained, which is recorded as 1# sodium salt.
[0084] According to IC test, SO in sodium pyrosulfate solid 3 The content is 154ppm; the chromaticity of 1# sodium salt tested by colorimeter is 21.1Hazen.
[0085] Test on 1# sodium salt 19 F-NMR and 11 B-NMR, and using NaBF 4 Compare with standard samples;
[0086] The peak positions of the NMR F spectrum are shown below:
[0087] Compound (I-1, M is Na): δ = -154.24 ppm
[0088] Compound (I-2, M is Na): δ = -150.21 ppm
[0089] The peak positions of the NMR B spectrum are shown below:
[0090] Compound (I-1, M is Na): δ = -0.64 ppm
[0091] Compound (I-2, M is Na): δ = -1.01 ppm
[0092] Standard NaBF 4 The NMR F spectrum peak δ = -159.94ppm; the NMR B spectrum peak δ = -0.89ppm.
[0093] To verify and confirm the compounds, compound (I-1, M is Na) and compound (I-2, M is Na), as well as NaBF 4 Theoretical calculations were performed. The DFT / B3LYP function and 6-31** basis set were used to optimize the structure of the compound, and the DFT / B3LYP function and 6-311** basis set were used to calculate the nuclear magnetic peak position of the above compound. The calculation results were compared with the test results, as well as LiBF 4 The NMR peak positions of the standard sample (F: δ = -159.94ppm, B: δ = -0.89ppm) were analyzed in coordination, and matched the above NMR spectrum results, which had a high degree of credibility. Therefore, it can be confirmed that the sodium salt #1 is mainly compound I-1 (M is Na) and also contains compound I-2 (M is Na).
[0094] By integrating and calculating the peak area of the NMR F spectrum, it can be seen that, in the sodium salt #1, excluding the amount of dimethyl carbonate, the mass content of compound (I-1) is 92.72wt%, and the mass content of compound (I-2) is 7.28wt%. Further area integration conversion is performed through the B spectrum, and it is found that the calculation results are consistent with the F spectrum, and the calculation reliability is high.
[0095] Comparative Example 1
[0096] In this comparative example, disiloxane sulfate and lithium hexafluorophosphate are used as raw materials to prepare lithium pyrosulfate, and pyrosulfate boron trifluoride composite metal salt is prepared by the lithium pyrosulfate, which specifically includes the following steps:
[0097] S1. In a drying room with a dew point of -40°C, add 1.0 mol of lithium hexafluorophosphate (LiPF6, purity 99.9%) to a reaction bottle, add ethyl methyl carbonate as a solvent, and the mass ratio of ethyl methyl carbonate to LiPF6 is 6:1, start stirring to mix the system evenly; then add bistrimethylsilyl sulfate to the reaction bottle in batches (control the reaction temperature not to exceed about 25°C), exhaust after each addition, add a total of 1.5 mol of bistrimethylsilyl sulfate, react at 25°C for 1 hour to obtain a reaction product;
[0098] S2. The reaction product was degassed under reduced pressure for 0.5 h to remove sulfur trioxide, phosphorus oxyfluoride and fluorosilane gases to obtain a crude product; isopropyl ether was added to the crude product as a crystallization solvent, and the mixture was stirred at 25°C for 1.5 h to precipitate crystals, which were allowed to stand and filtered. The filter cake was washed 2 to 3 times with isopropyl ether, and then heated and dried at 60°C under reduced pressure to obtain 94.5 g of a powdered lithium pyrosulfate product with a product yield of 99.47%;
[0099] Step S3 is the same as in Example 1. A pyrosulfate boron trifluoride composite lithium salt is obtained, which is recorded as lithium salt #6.
[0100] According to IC test, SO in lithium pyrosulfate solid 3 The content is 3512ppm; the chromaticity of 6# lithium salt tested by colorimeter is 546Hazen.
[0101] By integrating and calculating the peak area of the NMR F spectrum, it can be seen that in the 6# lithium salt, excluding the amount of dimethyl carbonate, the mass content of compound (I-1, M is Li) is 90.1wt%, and the mass content of compound (I-2, M is Li) is 8.9wt%. Further area integration conversion is performed through the B spectrum, and it is found that the calculation results are consistent with the F spectrum, and the calculation reliability is high.
[0102] Comparative Example 2
[0103] The operation of this comparative example is the same as that of Example 1, except that the calcination temperature in step S2 is adjusted from 150° C. to 320° C., and other operations remain unchanged. A pyrosulfate boron trifluoride composite metal salt is prepared and recorded as 7# lithium salt.
[0104] According to IC test, SO in lithium pyrosulfate solid 3 The content is 721ppm; the chromaticity of 7# lithium salt tested by colorimeter is 89.3Hazen.
[0105] By integrating and calculating the peak area of the NMR F spectrum, it can be seen that in the 7# lithium salt, excluding the amount of dimethyl carbonate, the mass content of compound (I-1, M is Li) is 89.5wt%, and the mass content of compound (I-2, M is Li) is 10.5wt%. Further area integration conversion is performed through the B spectrum, and it is found that the calculation results are consistent with the F spectrum, and the calculation reliability is high.
[0106] Comparative Example 3
[0107] The operation of this comparative example is the same as that of Example 6, except that the calcination temperature in step S2 is adjusted from 150° C. to 320° C., and other operations remain unchanged. A pyrosulfate boron trifluoride composite sodium salt is prepared, which is recorded as 2# sodium salt.
[0108] According to IC test, SO in sodium pyrosulfate solid 3 The content is 813ppm; the colorimeter test of 2# sodium salt shows that the chromaticity is 98.4 Hazen.
[0109] By integrating and calculating the peak area of the NMR F spectrum, it can be seen that in the 2# sodium salt, excluding the amount of dimethyl carbonate, the mass content of compound (I-1, M is Na) is 80.2wt%, and the mass content of compound (I-2, M is Na) is 19.8wt%. Further area integration conversion is performed through the B spectrum, and it is found that the calculation results are consistent with the F spectrum, and the calculation reliability is high.
[0110] Comparing the experimental results of Examples 1 to 5 and Comparative Example 1, it can be seen that compared with the preparation route using disiloxane sulfate and lithium hexafluorophosphate as raw materials, the pyrosulfate boron trifluoride composite lithium salt prepared in the present embodiment has a lower content of SO 3 Low content (SO in lithium pyrosulfate solids 3 During the synthesis process, it is transferred to the pyrosulfate boron trifluoride complex lithium salt product), and the product has low chromaticity.
[0111] 2. Electrolyte
[0112] Preparation of basic electrolyte 1: In a glove box filled with argon (water content <5ppm, oxygen content <10ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were uniformly mixed at a mass ratio of EC:EMC:DEC=4:4:2, and then lithium hexafluorophosphate (LiPF6) was slowly added to the mixed solution. 6 ) to a molar concentration of 1.0 mol / L to obtain basic electrolyte 1.
[0113] Preparation of basic electrolyte 2: In a glove box filled with argon (water content <5ppm, oxygen content <10ppm), propylene carbonate (PC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were uniformly mixed at a mass ratio of EC:EMC:PC=7:10:1, and sodium hexafluorophosphate (NaPF 6 ) to NaPF 6 The molar concentration is 1.0 mol / L, and basic electrolyte 2 is obtained.
[0114] Application Example 1
[0115] 0.2 wt % of 1# lithium salt was added to the basic electrolyte 1 to obtain the electrolyte of this application example.
[0116] Application Example 2
[0117] 1 wt % of 1# lithium salt was added to the basic electrolyte 1 to obtain the electrolyte of this application example.
[0118] Application Example 3
[0119] 2 wt % of 1# lithium salt was added to the basic electrolyte 1 to obtain the electrolyte of this application example.
[0120] Application Example 4
[0121] 3 wt % of 1# lithium salt was added to the basic electrolyte 1 to obtain the electrolyte of this application example.
[0122] Application Example 5
[0123] 1 wt % of 2# lithium salt was added to the basic electrolyte 1 to obtain the electrolyte of this application example.
[0124] Application Example 6
[0125] 1 wt % of 3# lithium salt was added to the basic electrolyte 1 to obtain the electrolyte of this application example.
[0126] Application Example 7
[0127] 1 wt % of 4# lithium salt was added to the basic electrolyte 1 to obtain the electrolyte of this application example.
[0128] Application Example 8
[0129] 1 wt % of 5# lithium salt was added to the basic electrolyte 1 to obtain the electrolyte of this application example.
[0130] Application Example 9
[0131] 1 wt % 1# lithium salt and 1 wt % vinylene carbonate (VC) were added to the basic electrolyte 1 to obtain the electrolyte of this application example.
[0132] Application Example 10
[0133] 1 wt % 1# lithium salt and 1 wt % 1,3-propane sultone (PS) were added to the basic electrolyte 1 to obtain the electrolyte of this application example.
[0134] Application Example 11
[0135] 1 wt% 1# lithium salt and 1% wt dithiothreitol (DTD) were added to the basic electrolyte 1 to obtain the electrolyte of this application example.
[0136] Application Example 12
[0137] 1 wt % 1# sodium salt was added to the basic electrolyte 2 to obtain the electrolyte of this application example.
[0138] Application Comparative Example 1
[0139] 1 wt % of 6# lithium salt was added to the basic electrolyte 1 to obtain the comparative electrolyte of this application.
[0140] Application Comparative Example 2
[0141] 1 wt % of 7# lithium salt was added to the basic electrolyte 1 to obtain the comparative electrolyte of this application.
[0142] Application Comparative Example 3
[0143] The basic electrolyte 1 was not treated in any way to obtain the comparative electrolyte of this application.
[0144] Application Comparative Example 4
[0145] 1 wt % 2# sodium salt was added to the basic electrolyte 2 to obtain the comparative electrolyte of this application.
[0146] Application Comparative Example 5
[0147] The basic electrolyte 2 was not treated in any way to obtain the comparative electrolyte of this application.
[0148] 2. Electrochemical performance test
[0149] The electrolytes of the above-mentioned application examples 1 to 11 and the application comparative examples 1 to 3 are respectively made into soft-pack lithium-ion batteries with a capacity of 1260 mAh. The lithium-ion batteries include a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and battery auxiliary materials. The positive electrode active material is a ternary positive electrode LiNi 0.6 Co 0.2 Mn 0.2 O 2The negative electrode active material is high-capacity graphite. The preparation process is as follows: the positive electrode sheet, the separator and the negative electrode sheet are wound together into a roll core, sealed with an aluminum plastic film and then baked to make the electrode moisture meet the requirements, and the battery cell is injected with electrolyte after baking, and the finished lithium-ion battery soft pack battery cell is obtained through the steps of standing, forming, capacity separation and aging.
[0150] The electrolytes of the above-mentioned application example 12 and the application comparative examples 4-5 are respectively made into soft-pack sodium ion batteries with a capacity of 1260 mAh. The sodium ion batteries include a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and battery auxiliary materials. The positive electrode active material is a ternary positive electrode NaNi 0.33 Fe 0.33 Mn 0.33 O 2 The negative electrode active material is hard carbon. The preparation process is as follows: the positive electrode sheet, the separator and the negative electrode sheet are wound together into a roll core, sealed with an aluminum plastic film and then baked to make the electrode moisture meet the requirements, and the battery cell is injected with electrolyte after baking, and the finished sodium ion soft-pack battery cell is obtained through the steps of standing, forming, volume separation and aging.
[0151] The performance test (test voltage 2.8-4.2V) of the lithium ion battery and sodium ion battery prepared above mainly includes:
[0152] (1) 60°C high temperature storage test: The battery was charged to 100% SOC and stored in a 60±2°C oven for 28 days. The volume before and after storage was measured to obtain the volume expansion rate of the single battery before and after 60°C storage. The DCR value after storage was measured at room temperature, and the percentage value of the initial DCR was calculated and recorded as the discharge DCR change rate.
[0153] (2) 45°C high temperature cycle test: The battery is cycled in a 45±1°C oven at a charge and discharge current of 1C / 1C. The discharge capacity per week is calculated. The cycle is stopped after 500 cycles, and the capacity retention rate after the cycle is calculated.
[0154] (3) -20℃ low-temperature discharge: The battery is discharged in a -20±1℃ oven at a discharge current of 1C to 80% of the lower limit voltage. The low-temperature discharge capacity is taken as the percentage of the 1C discharge capacity at 25℃, which is recorded as the low-temperature discharge capacity retention rate.
[0155] Table 1 Electrochemical performance test results
[0156]
[0157] According to Table 1 above, by comparing Application Example 2, Application Examples 5-8 and Application Comparative Examples 1-3, or comparing Application Example 12 with Application Comparative Examples 4 and 5, the use of low SO 3The pyrosulfate boron trifluoride composite metal salt prepared using pyrosulfate with a low content as a raw material has low chromaticity, can inhibit the gas production and impedance growth during high-temperature storage, and improve low-temperature performance.
[0158] Further comparison of Application Example 2, Application Example 7 and Application Comparative Example 2 shows that as the calcination temperature increases, the SO 3 The content and chromaticity of the prepared pyrosulfate boron trifluoride composite lithium salt are both increasing, while its electrochemical performance in lithium-ion battery electrolyte is showing a downward trend. The reason is that the increase in calcination temperature causes part of the lithium pyrosulfate to decompose and produce SO 3 , resulting in SO 3 The content of SO 3 It promotes the occurrence of electrolyte / electrode side reactions in the battery, causing its electrochemical performance to deteriorate.
[0159] By comparing Application Example 2 and Application Example 9, it can be found that adding 1# lithium salt and VC to the electrolyte at the same time can not only avoid the defect of VC increasing the initial impedance of the battery, but also further improve the high-temperature storage performance and cycle performance; by comparing Application Example 2 and Application Example 10, it can be found that adding 1# lithium salt and PS to the electrolyte at the same time can not only give play to the advantage of PS significantly inhibiting the gas production of the battery during high-temperature storage, but also avoid the defect of PS increasing the initial impedance and deteriorating the low-temperature performance.
[0160] By comparing application examples 1 to 4, it can be found that with the gradual increase in the amount of 1# lithium salt added, within a certain addition range, the overall performance of the battery gradually improves; but with the further increase in the addition amount, the battery performance cannot continue to improve, and the optimal addition amount is around 1wt% to 2wt%.
Claims
1. A method for preparing a low-chroma pyrosulfate boron trifluoride composite metal salt, characterized in that: The preparation method comprises: in a reaction solvent, using pyrosulfate with a SO3 content of ≤500ppm as a raw material, reacting with boron trifluoride gas or a boron trifluoride complex to obtain a reaction solution with a chromaticity of ≤50 Hazen, wherein the reaction solution at least comprises a pyrosulfate boron trifluoride composite metal salt having a structure shown in the following formula (I-1): Wherein, M is Li or Na.
2. The method for preparing the low-chroma pyrosulfate boron trifluoride composite metal salt according to claim 1, characterized in that: The pyrosulfate raw material is prepared by the following steps: (1) a step of preparing a bisulfate salt: an inorganic salt is reacted with dilute sulfuric acid to obtain a bisulfate salt, wherein the inorganic salt is selected from at least one of sulfate, metal oxide, carbonate, metal hydroxide or bicarbonate; and the bisulfate salt is sodium bisulfate or lithium bisulfate; (2) Preparation step of pyrosulfate: The hydrogen sulfate solid is decomposed by heat to obtain pyrosulfate, wherein the pyrosulfate is lithium pyrosulfate or sodium pyrosulfate.
3. The method for preparing the low-chroma pyrosulfate boron trifluoride composite metal salt according to claim 2, characterized in that: In step (1), the mass concentration of dilute sulfuric acid is 10% to 65wt%.
4. The method for preparing the low-chroma pyrosulfate boron trifluoride composite metal salt according to claim 2, characterized in that: In step (1), the molar ratio of the inorganic salt to the dilute sulfuric acid is (0.8-1.2):
1.
5. The method for preparing the low-chroma pyrosulfate boron trifluoride composite metal salt according to claim 2, characterized in that: In step (1), the reaction temperature is 0 to 80° C. and the reaction time is 0.5 to 24 h.
6. The method for preparing the low-chroma pyrosulfate boron trifluoride composite metal salt according to claim 2, characterized in that: In step (2), the hydrogen sulfate solid is calcined at 100 to 300° C. for 0.5 to 72 h to obtain pyrosulfate.
7. The method for preparing the low-chroma pyrosulfate boron trifluoride composite metal salt according to claim 6, characterized in that: In step (2), the hydrogen sulfate solid is calcined at 130-250° C. for 2-36 hours to obtain pyrosulfate.
8. The method for preparing a low-chroma pyrosulfate boron trifluoride composite metal salt according to any one of claims 1 to 7, characterized in that: The SO3 content in the pyrosulfate raw material is ≤200ppm.
9. The method for preparing the low-chroma pyrosulfate boron trifluoride composite metal salt according to claim 1, characterized in that: The reaction solvent is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl acetate, ethyl acetate, methyl propionate, γ-butyrolactone, ethyl ether, ethylene glycol dimethyl ether, acetonitrile, benzyl cyanide or propionitrile.
10. The method for preparing the low-chroma pyrosulfate boron trifluoride composite metal salt according to claim 1, characterized in that: The boron trifluoride complex is selected from at least one of a boron trifluoride ethyl ether complex, a boron trifluoride glycol dimethyl ether complex, a boron trifluoride dimethyl carbonate complex, a boron trifluoride pyridine complex, a boron trifluoride ethylamine complex, a boron trifluoride butyl ether complex, a boron trifluoride methyl ether complex, a boron trifluoride acetonitrile complex, a boron trifluoride piperidine complex, a boron trifluoride phenol complex, a boron trifluoride tetrahydrofuran complex, a boron trifluoride dimethyl sulfide complex or a boron trifluoride morpholine complex.
11. The method for preparing the low-chroma pyrosulfate boron trifluoride composite metal salt according to claim 1, characterized in that: During the reaction of pyrosulfate with boron trifluoride gas or boron trifluoride complex, the molar ratio of pyrosulfate to boron trifluoride gas or boron trifluoride complex is (0.33-1.0):1, the reaction temperature is 40-70°C, and the reaction time is 5-24h.
12. The method for preparing the low-chroma pyrosulfate boron trifluoride composite metal salt according to claim 11, characterized in that: The reaction solution contains at least 80 wt% or more of the pyrosulfate boron trifluoride composite metal salt having the structure represented by the formula (I-1), and the rest is at least one of the compounds represented by the following formulas (I-2), (I-3), (I-4), (I-5), and (I-6): In formulas (I-2), (I-3), (I-4), (I-5), and (I-6), M is Li or Na.
13. The method for preparing the low-chroma pyrosulfate boron trifluoride composite metal salt according to claim 12, characterized in that: The reaction solution contains 80-95 wt % of the pyrosulfate boron trifluoride composite metal salt having the structure represented by formula (I-1).
14. Use of the low-chroma pyrosulfate boron trifluoride composite metal salt prepared by the preparation method according to any one of claims 1 to 13 in an electrolyte, characterized in that: The prepared low-color pyrosulfate boron trifluoride composite metal salt is added to the electrolyte so that its mass percentage in the electrolyte is 0.01-15wt%.
Citation Information
Patent Citations
Preparation method of lithium pyrosulfate
CN118026224A
Application of pyrosulfate boron trifluoride composite lithium salt in electrolyte
CN118173890A